Traditional Malay Pottery of Kuala Kangsar: Its History and Development - Azmi Arifin, (Kajian Malaysia, 2015)
This essay discusses the pottery-production heritage of Kuala Kangsar, in particular the labu sayong (earthen ware or gourd pitchers from the Sayong area). This particular handicraft of the Perak Malays has a unique history of its own. From the historical aspect, the practice of pottery-production is believed to have started by the Malays thousands of years ago. Over the years the heritage has been kept alive and is still being practiced traditionally by Malays in Kuala Kangsar and produced for commercial purposes. Confronted with the emergence of new and modern pottery-production techniques, which is a challenge to the popularity of traditional pottery, the traditional technique of pressing and pinching has been sustained until the present day. Based on historical and archaeological sources and field study, this essay explains the origins, history and development of pottery-production in Kuala Kangsar. The essay also identifies the problems and challenges which traditional labu sayong practitioners have to face and steps taken by the government to ensure this traditional Malay handicraft is safeguarded and sustained so that it is not wiped out by changes over time.